Electrical stimulation increases hypertrophy and metabolic flux in tissue-engineered human skeletal muscle. (April 2019) - Khodabukus, Alastair; Madden, Lauran; Prabhu, Neel K.; Koves, Timothy R.; Jackman, Christopher P.; Muoio, Deborah M.; Bursac, Nenad
Abstract: In vitro models of contractile human skeletal muscle hold promise for use in disease modeling and drug development, but exhibit immature properties compared to native adult muscle. To address this limitation, 3D tissue-engineered human muscles (myobundles) were electrically stimulated using intermittent stimulation regimes at 1 Hz and 10 Hz. Dystrophin in myotubes exhibited mature membrane localization suggesting a relatively advanced starting developmental maturation. One-week stimulation significantly increased myobundle size, sarcomeric protein abundance, calcium transient amplitude (∼2-fold), and tetanic force (∼3-fold) resulting in the highest specific force generation (19.3mN/mm 2 ) reported for engineered human muscles to date. Compared to 1 Hz electrical stimulation, the 10 Hz stimulation protocol resulted in greater myotube hypertrophy and upregulated mTORC1 and ERK1/2 activity. Electrically stimulated myobundles also showed a decrease in fatigue resistance compared to control myobundles without changes in glycolytic or mitochondrial protein levels. Greater glucose consumption and decreased abundance of acetylcarnitine in stimulated myobundles indicated increased glycolytic and fatty acid metabolic flux. Moreover, electrical stimulation of myobundles resulted in a metabolic shift towards longer-chain fatty acid oxidation as evident from increased abundances of medium- and long-chain acylcarnitines. Taken together, our study provides an advanced in vitro model of human skeletal muscle with improved structure, function, maturation, and metabolic flux.